First-Year Students' Understanding of The Use of Differential and Integral in Solving Kinematics Problems - Sarkity, Dios; Fitriani, Rita; Kurniawan, Bakhrul Rizky (Universitas Lambung Mangkurat, 2025)
A good interconnection between mathematical ability and understanding of physics concepts is needed to solve physics problems. This study aims to analyze students' initial understanding of differential and integral concepts and students' understanding of using differential and integral in solving kinematic problems. This study involved 23 first-year Chemistry Education Study Program students taking a General Physics Course. The study was conducted in May 2024. This study was a descriptive study with a quantitative approach. Test was used to collect data with essay questions as an instrument. The instruments used are valid and reliable, with a reliability coefficient 0.74. Data were analyzed using descriptive statistics. The results showed that the number of students who understood the concept of differential was twice as many as those who understood the concept of integral. The results also showed that the number of students who could apply the concept of differential in solving physics problems was much greater than the number of students who could apply the concept of integral in solving physics problems. Even so, there was the much greater number of students who did not understand mathematical concepts and could not apply them in solving physics problems. This indicates the importance of strengthening mathematical concepts to support the implementation of physics learning. This can be conducted by involving students in problem-solving learning using real-life physics problems. Students must use their mathematical abilities and appropriate physics concepts to find the solutions. It will help students understand the interconnection between mathematics and physics so that they can see both as one inseparable part.